(untitled) (Plant Tissue Culture and Biotechnology, 2020)
Cotyledonary leaf and node of two varieties, namely red and yellow of Bell pepper (Capsicum annuum L.) were cultured in MS with different concentrations and combinations of plant growth regulators. The cotyledonary leaf was found to be most responsive towards multiple shoot regeneration. The leaf explants of red variety showed best result towards shoot regeneration in MS with BAP (8.0 mg/l), NAA (0.02 mg/l) and IAA (1.0 mg/l). Eighty per cent explants responded within 13 - 14 days, and the mean number of shoot per explant was was found to be 5.67. The cotyledonary leaf explants of yellow variety showed promising result when the cotyledonary leaf explant was cultured in MS with BAP (8.0 mg/l) and NAA (0.5 mg/l) being the mean number of shoot per explants 5.13 and 70% of them responded within 14 - 15 days. Maximum root induction was found in MS with IBA (0.5 mg/l) in both capsicum varieties. After successful root formation plantlets were transplanted and acclimatized to the soil. Plant Tissue Cult. & Biotech. 30(2): 267-275, 2020 (December)